COMPARISON OF SAFETY AND EFFECTIVENESS BETWEEN LAPAROSCOPIC AND OPEN PANCREATODUODENECTOMY: A SYSTEMATIC REVIEW - Muhammad, Iqbal (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Despite using open and laparoscopic pancreatoduodenectomy methods. However, clinicians worldwide are still unsure regarding laparoscopic adoption. This technique's challenging dissection and anastomosis may explain this. The oncological outcomes of open and laparoscopic pancreatoduodenectomy are uncertain and maybe disputed. The procedure uses these methods. The aim: This article compared safety and effectiveness between laparoscopic and open pancreatoduodenectomy. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 176 articles, whereas the results of our search on SagePub brought up 82 articles. The results of the search conducted for the last year of 2013 yielded a total 43 articles for PubMed and 21 articles for SagePub. In the end, we compiled a total of 27 papers, 19 of which came from PubMed and eight of which came from SagePub. We included seven research that met the criteria. Conclusion: Studies show that LPD is associated with good short-term outcomes, high survival rates, short length of stay, and less bleeding. The operating time for patients with LPD is longer than for patients with OPD.